2019
DOI: 10.1007/s13238-019-0612-5
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrion-processed TERC regulates senescence without affecting telomerase activities

Abstract: Mitochondrial dysfunctions play major roles in ageing. How mitochondrial stresses invoke downstream responses and how specificity of the signaling is achieved, however, remains unclear. We have previously discovered that the RNA component of Telomerase TERC is imported into mitochondria, processed to a shorter form TERC-53 , and then exported back to the cytosol. Cytosolic TERC-53 levels respond to mitochondrial functions, but have no direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 49 publications
0
40
1
1
Order By: Relevance
“…It was detected by the RT-PCR in purified mitoplasts, but as as a shorter, 195 nt-long transcript, which was termed TERC-53. Zheng et al (2019) demonstrated that TERC-53 is mostly localized in the cytosol, where it regulates cellular senescence and is involved in cognition decline in mice hippocampus without affecting telomerase activity or mitochondrial functions. Having this in mind, the authors hypothesized that TERC-53 is exported from the mitochondria back to the cytosol (Cheng et al, 2018;Zheng et al, 2019).…”
Section: Housekeeping Ncrnas Localized In Mitochondriamentioning
confidence: 99%
“…It was detected by the RT-PCR in purified mitoplasts, but as as a shorter, 195 nt-long transcript, which was termed TERC-53. Zheng et al (2019) demonstrated that TERC-53 is mostly localized in the cytosol, where it regulates cellular senescence and is involved in cognition decline in mice hippocampus without affecting telomerase activity or mitochondrial functions. Having this in mind, the authors hypothesized that TERC-53 is exported from the mitochondria back to the cytosol (Cheng et al, 2018;Zheng et al, 2019).…”
Section: Housekeeping Ncrnas Localized In Mitochondriamentioning
confidence: 99%
“…Similarly to RMRP, hTERC was found to be processed upon mitochondrial import into a shorter 195 nt-long RNA termed TERC-53. Since the processed version of hTERC was detected mostly in the cytosol, the authors suggested that TERC-53 is re-exported from the mitochondria, which would permit to somehow relay the functional state of the mitochondria to the nucleus and other cellular compartments [25,70]. However, evidence that hTERC processing occurs within the mitochondrial matrix and not at the mitochondrial surface is currently lacking.…”
Section: Mitochondrial Rna Importomementioning
confidence: 99%
“…Interestingly, the majority of TERC-53 has been detected in the cytosol instead of mitochondria, and the cytosolic levels of TERC-53 are regulated by mitochondrial functions but have no direct effect on mitochondria (Cheng et al, 2018; Figure 3). The following studies showed that TERC-53 functions as a signaling molecule, relating the functional states of mitochondria to the nucleus, possibly by inhibiting GAPDH nuclear translocalization (Zheng et al, 2019). TERC-53 itself does not affect and is independent of telomerase activity (Zheng et al, 2019).…”
Section: Mitochondrial Localization and Processing Of Tercmentioning
confidence: 99%
“…The following studies showed that TERC-53 functions as a signaling molecule, relating the functional states of mitochondria to the nucleus, possibly by inhibiting GAPDH nuclear translocalization (Zheng et al, 2019). TERC-53 itself does not affect and is independent of telomerase activity (Zheng et al, 2019). The whole process of TERC-53 production and function has been shown to be involved in cellular senescence and organismal aging (Zheng et al, 2019; Figure 3).…”
Section: Mitochondrial Localization and Processing Of Tercmentioning
confidence: 99%
See 1 more Smart Citation